The Extent and Nature of Potential Flood Damage to Commercial Property Structures in the Midwestern United States. (5th September 2017) - Shultz, Steven
Abstract: Prior research on the extent of potential flood damage in the U.S. has focused on single‐family residential structures, whereas this study evaluates the extent and nature of potential flood damage to commercial structures in two locations. Commercial buildings represent 13% of all structures in the 100‐year floodplain in Sarpy County (Omaha, NE) and 16% in Fargo/Moorhead (ND and MN), yet account for half of total potential flood damage exposure as represented by depreciated structural replacement values (DSRVs). The most frequent commercial structures are special use, warehouse, and industrial properties, which are all well suited to DSRVs estimation. Commercial building characteristics are highly heterogeneous, making the extrapolation of their potential flood damage based on sample observations problematic. Commercial floodplain structures are older and/or less maintained and less valuable than non‐floodplain structures, which, combined with the fact that higher valued multiple family, retail, and office structures were relatively rare in the 100‐year floodplain, indicates that commercial property owners in general exhibit rational flood risk avoidance.